Cost X-efficiency and Loan Loss Provision Decision: Evidence from Mainland China and Hong Kong Listed Banks - Yang, Jiajia (2014)
This paper examined Loan Loss Provision (LLP) determinants: business cycle, income smoothing, capital management, signalling effect and also cost X-efficiency, using 18 Mainland Chinese and 9 Hong Kong(HK) listed banks from 2006 to 2013 within two stages. To test the impact of efficiency on LLP, the first stage is carried out generating cost efficiency scores for individual banks in each year using cost translog function. The second stage then tests the determinacy of LLP using main determinants variables via the feasible efficient GMM model. Empirical results support countercyclical behaviour and income smoothing however fail to support capital management and signalling effect. More interestingly, cost efficiency is found its influence on LLP determinacy: a negative relationship.